1998
DOI: 10.1021/bi972811u
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of an Intramolecular DNA Triplex Containing 5-(1-Propynyl)-2‘-deoxyuridine Residues in the Third Strand,

Abstract: Incorporation of the modified base 5-(1-propynl)-2'-deoxyuridine (propynylU) in the third strand of a triplex leads to enhanced triplex stabilization. To investigate effects of the propyne nucleotide on triplex structure and the factors underlying the increased stability, we have determined the solution structure of the intramolecular DNA pyrmidine-purine-pyrimdine d(AGAGAGAA-(EG)6-TTCTCTCT-(EG)6-PCPCPCPP) (PDD-EG), which contains 5-(1-propynl)-2'-deoxyuridine (P) in the third strand and hexakis(ethylene glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 44 publications
(60 reference statements)
3
34
0
Order By: Relevance
“…A similar effect is seen with 5-propynyl-U, Fig. (5a), which also increases triplet stability [73][74][75], though 5-propynyl-C produces a less stable triplet since this substitution further reduces the pK of N3 to 3.3. The increased stability of 5-propynyl substituted bases is presumably due to increased base stacking interactions.…”
Section: Improved Base Stackingmentioning
confidence: 54%
See 1 more Smart Citation
“…A similar effect is seen with 5-propynyl-U, Fig. (5a), which also increases triplet stability [73][74][75], though 5-propynyl-C produces a less stable triplet since this substitution further reduces the pK of N3 to 3.3. The increased stability of 5-propynyl substituted bases is presumably due to increased base stacking interactions.…”
Section: Improved Base Stackingmentioning
confidence: 54%
“…However, simple addition of aromatic rings to the pyrimidine nucleus does not seem to be of benefit [76][77][78][79], possibly because the improved stacking of the single stranded oligonucleotide hinders triplex formation. Other stacking interactions, such as those involving appended propynyl or propargylamino groups [72][73][74][75], may be a better option. Lastly it is possible that different sugars should be used for third strand C or T, since it appears that rigid linkers improve the stability of T q AT, while flexible linkers improve the stability of C +q GC [35,36].…”
Section: Future Prospectsmentioning
confidence: 99%
“…The ability of C5-propynyl-2′-deoxyuridine (i.e. with no appended cations to the nucleobase) to stabilize triple helices through enhanced base stacking is well-documented (36,37). In DNA duplexes and triplexes, a C5-propynyl-modified cytosine or uracil can enhance stability (7).…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier work we found that a patch of 3-4 contiguous 2′-AE residues made an important contribution towards the bioactivity of TFOs containing 2′-O-Me ribose sugars 23,30. Accordingly we synthesized TFO- 15 with 2′-O-Me ribose, four contiguous 2′-AE residues at the 3′ end, and the alternating distribution pattern of 2 found in TFO- 12 .…”
Section: Resultsmentioning
confidence: 94%
“…However, when we determined the k on value for TFO- 15 we found a pronounced decline relative to the TFO- 14 control. This was unexpected since both the 2′-AE cluster,30 and the alternating pattern of 2 (Table 2) enhance association rate relative to TFOs containing only the 2′-O-Me modification. Given the importance of the association rate as a correlate of TFO bioactivity, we examined the properties of two additional TFOs containing 2′-AE and 2′-O-Me ribose.…”
Section: Resultsmentioning
confidence: 97%